Wildlife Utilization of Salt Lick in Selected Areas in Sarawak - Hidayah, Nurul-Asna (University Malaysia Sarawak, 2021)
Salt lick is an important part of wildlife survival supporting the nutritional needs lacking in wildlife diet. To date, little documentation is available on salt licks in Sarawak which is not protected under legislation as compared to other salt licks in Malaysia. This study aims to understand salt licks from three different perspectives: wildlife dynamics, mineral composition and local social economy. Nine salt licks located at the northwest of Sarawak were selected for this study. Camera trapping was utilised to document wildlife dynamics on salt licks reporting a total of 25 species utilising salt lick for mineral supplementation. A percentage of 68% (n=17) were listed either as Totally Protected or Protected in Wild Life Protection Ordinance 1998. Soil samples were collected from nine salt licks, where one sample is taken from the salt lick itself and a sample for every 100 m interval up to 500 m. Samples were digested through acid digestion and analysed using an atomic absorption spectrometer. The concentrations of macronutrients across nine salt licks are within the range of nd - 117 mg/kg for Na, 482.96 - 3514.07 mg/kg for Mg, 427.40 – 1499.64 mg/kg for K, nd – 748.33 mg/kg for Ca and the concentrations were observed to reduce horizontally moving further away from the salt licks. Quantitative questionnaire survey using snowball sampling method was conducted in all communities surrounding the nine salt licks comprising of the Iban, Kenyah, Berawan and Kelabit communities. They were found to use salt lick predominantly as hunting grounds with 57.14% reported to catch 1-2 animals per each hunting visit to salt licks. The examination data of this study can be used to suggest suitable conservation buffer for salt lick conservation and holistic management plans by including wildlife, chemical and social perspective for salt licks in Sarawak.